EVALUASI KURIKULUM PEMBELAJARAN BAHASA ARAB UNTUK PERBAIKAN MUTU AKADEMIK DI MI MAMBAUL MA’ARIF - Uswatun Chasanah; Andi Prastowo (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
Abstract: The research was conducted to find out the form of instruments used in the evaluation of the Arabic language learning curriculum in MI. This study uses a case study method at MI Mambaul Ma'arif. The research subject of the teacher of Arabic subjects. Data collection techniques with interviews, observations, and documentation studies. The data analysis technique is carried out by inductive analysis techniques. The results revealed that there are four types of curriculum evaluation, namely formative evaluation, summative evaluation, input evaluation, and product evaluation. The instrument forms used are test and nontest. Test instruments are classified into nen types, and twelve types of non-test types. The selection of instrument forms must be following the needs and characteristics of the learners. And teachers have no difficulty in making and implementing these forms of instruments when conducting evaluations either in the form of tests or nontests. If the results shown have not reached the minimum standard, it is necessary to provide follow-up in the form of remedial activities. And if it has reached the minimum standard, enrichment activities may be given.